Ablation for idiopathic left ventricular tachycardia in a patient with double outlet right ventricle who underwent Fontan operation: a case report. Issue 5 (7th September 2020) - Miyamoto, Masakazu; Nishii, Nobuhiro; Morita, Hiroshi; Ito, Hiroshi
Abstract: Background: The incidence of ventricular tachycardia (VT) in patients following Fontan operation is reported as 3.5%. Furthermore, in patients with repaired double outlet right ventricle (DORV), scar-related VT and outflow tract VT have been reported; however, Purkinje-related VT has not previously been reported. In this report, we present the case of idiopathic left VT (ILVT) in a patient with DORV who underwent Fontan operation. Case summary: A 31-year-old man was diagnosed as having DORV with complete atrioventricular defect at birth. When he was 17 years old, he underwent surgical repair, including extracardiac Fontan operation and common atrioventricular valve replacement. Five years later, VT was detected. Since some medications were ineffective in suppressing VT, he was referred to our hospital for definitive treatment. Ventricular tachycardia was induced by atrial and ventricular programmed electrical stimulations. The mechanism of the VT was determined to be re-entry. The earliest activation site was located at the mid-inferior septum of the hypoplastic left ventricle, in which Purkinje potentials were observed before the local ventricular electrogram. Radiofrequency catheter ablation (RFCA) was performed at this site to eliminate VT. Discussion: Most VTs originate from surgical scars in patients with congenital heart disease. Catheter ablation was feasible in scar-related VT. To the best of our knowledge, this is the first report of ILVT treated successfully with RFCA in a DORV patient who had undergone Fontan operation.